Detection of Toxoplasma gondii in the milk of experimentally infected Wistar female rats - Costa, V. M. [UNESP]; Langoni, Hélio [UNESP] (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2010)
The milk of experimentally infected rats was investigated for the presence and possible transmission of Toxoplasma gondii. Wistar (Rattus norvegicus) female rats were divided into three groups and orally inoculated with bradyzoites. Polymerase chain reaction (PCR) was employed to detect the parasite in the milk. Transmission to the offspring was verified by indirect immunofluorescence antibody test (IFAT), modified agglutination test (MAT), bioassay tests and PCR. Rat milk samples were PCR-positive, pups were serum-reactive to T. gondii and tissue samples also presented positive DNA results through PCR.
Keywords: Toxoplasma gondii; parasite in milk; female rats; PCR; bioassay